Dynamisches Bremsverhalten des Reifen-Fahrwerk-Systems - Zhou, Yaoqun (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
In the frame of this research work, a complete tyre suspension brake system, which includes a McPherson strut and a modified ABS hydro aggregate is analyzed, developed and optimized on the inner drum test bench and studied using different tyres as well as under various road and braking excitations. By direct control of each interior magnet valve in the ABS hydro aggregate by a real time computer, complex brake slopes as well as various ABS control concepts are implemented on the test bench.